Implementasi Trainer Kit Pembangkit Listrik Tenaga Surya sebagai Pengembangan Media Pembelajaran Instalasi Listrik - Partaonan Harahap; Muhammad Adam; Balisranislam Balisranislam (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2021)
This solar power generator system trainer is designed with a modular concept, where each component is packaged and made separately with an attractive design, equipped with the name of the component and various information about the component so that it will be easy to use, maintain and most importantly is that it can facilitate understanding the concept of the system and installation of solar power generation system units because it can be installed and assembled repeatedly, in the tests and calculations that have been carried out, on the PLTS trainer kit tool as the development of learning media for electrical installations that can be obtained at the panel surface temperature. (Tp) the average radiation is 917.9 W/m, this shows that the radiation tends to decrease because the weather is cloudy and wind gusts occur, with an average voltage of 18.97 Volts and a current of 1.8 A. PLTS is made to scale laboratory with tilt angle adjustable solar panel module and panel position to get the value of measurement parameters such as light intensity, solar panel voltage, battery voltage, battery charging current, DC output voltage, and AC inverter voltage.